The Effectiveness of Acceptance and Commitment Therapy on Pain Control and Adherence to Treatment in Dialysis Patients - Amir Hossein Sadeghi; Abbas Ghodrati-Torbati; Hamideh Yaghoubi; Seyed Ali Ahmadi (Gonabad University of Medical Sciences, 2023)
Background: Pain control and adherence to treatment is one of the most common problems in dialysis patients. Psychological treatments can be effective in reducing the problems of these patients. This study attempted to investigate the effectiveness of acceptance and commitment therapy (ACT) on pain control and adherence to treatment among dialysis patients. Methods: It was a semi-experimental pre-test, post-test study with a control group. The statistical population consisted of 40 people who were referred to a dialysis clinic in 2022 and an available sampling method was used to select and randomly assign patients to two experimental and control groups. In the experimental group, ACT was performed in eight sessions of 90 minutes. McGill pain questionnaire (MPQ) and adherence to treatment scale were used. Data were analyzed using SPSS software, version 21 and analysis of covariance. Results: There was a significant difference between the mean scores of pain control and adherence to treatment in the two experimental and control groups (p<0.05). The effect of this treatment on increasing the pain control score was 51% and on increasing the adherence to treatment score was 44%. Conclusion: ACT can increase pain control and adherence to treatment in dialysis patients; thus, it can be used in designing treatment plans for dialysis patients.